The Determining Factors for Establishing the Structure of Agricultural Crops in Small Farms in Romania - Marius Daniel NICULA; Dumitrache Bogdan BRATOVEANU; Petre Adrian LIPTAC; Raluca Beatrice COSTEA (VOINEA); Iuliana Manuela DUMITRIU (ION); Cristina STOICA (DINCĂ); Silvius STANCIU (Communications of International Proceedings, 2020)
The crop structure of a farm designates its field of activity and, in the case of developing a strategy, it is a component of it, influencing in many aspects the results that will be obtained. Due to its complexity, determined by the multitude of components, the relationships between it and the impact it generates on the economy of agricultural holdings, the culture structure has a special decision charge. In this context, the structure can be viewed as a combination of options, of ways in which the unit is to function. It is absolutely necessary for the process of establishing a culture structure to take into account the relationships of biological, technological and economic nature, whose contents can lead to either a complex structure of production (diversification) or the imposition of narrowing the profile of the production activity (specialization). The following indicators are followed in research: structure of cultures (2015-2018); cultivated area (2015-2018) and total production, prices and total revenues (2015-2018). The conclusion of the research is that choosing an optimal crop structure, it starts from the soil and climate conditions that characterize the agricultural unit, following on one hand, putting them into value, and on the other hand satisfying the requirements of the plants towards these factors, which influences the level of production. Extensive and intensive agriculture determines the organization of different production structures, with particularities that influence the economic results on the farm level. Practicing culture structure is a natural consequence of the plant biology, especially population’s need for food (population growth and product demand).
Keywords: Agriculture; Culture Structure; Culture Share.